SOME RELATIONS BETWEEN JACOBI AND BESSEL POLYNOMIALS - Popov, Blagoj S. (Matematichki Bilten, 1999)
Using a classical method, the expansion of an orthogonal polynomial in a series of other system of orthogonal polynomials, is given.